2010
DOI: 10.2478/s11687-010-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

New host report for nematodes in a stranded short-snouted spinner dolphin Stenella clymene (Cetacea: Delphinidae) from the Mexican Caribbean coast

Abstract: SummaryOne short-snouted spinner dolphin Stenella clymene individual stranded on the coast of Quintana Roo, Mexico, was examined for stomach and lung nematodes. During necropsy, a large number of nematodes of the species Skrjabinalius guevarai were found in the airways. Additionally, some larval Anisakis sp. were found in the stomach. Both nematode species are reported for the first time from this host. The present is the first helminthological study of the short-snouted spinner dolphin in Mexico and adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Data from previous field surveys reporting quantitative data on any of the lungworm species detected in this study are shown in Additional file 3 : Table S3; further qualitative records did not increase the number of infected species (data not shown). All records concern the Atlantic [ 43 – 49 ] and Pacific Oceans [ 50 – 58 ] and the Mediterranean Sea [ 59 , 60 ]. Halocercus delphini and S. globicephalae were found in 7 species and S. ovatus in 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data from previous field surveys reporting quantitative data on any of the lungworm species detected in this study are shown in Additional file 3 : Table S3; further qualitative records did not increase the number of infected species (data not shown). All records concern the Atlantic [ 43 – 49 ] and Pacific Oceans [ 50 – 58 ] and the Mediterranean Sea [ 59 , 60 ]. Halocercus delphini and S. globicephalae were found in 7 species and S. ovatus in 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After clarification, internal and external structures were visualized under an optical microscope and measured by using a micrometric ocular. Parasite identification was based on morphological identification keys available in the literature [ 11 , 12 , 20 , 23 , 30 , 32 , 35 , 37 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lungworm nematodes H. delphini (identified as Skrjabinalius guevarai Gallego and Selva, 1979;see Pool et al, 2020) were reported in the airways of a Clymene dolphin found stranded on the Caribbean coast of Mexico by Aguilar-Aguilar et al (2010). Carvalho et al (2010) reported H. brasiliensis Almeida, 1933 andHalocercus sp. in the lungs of a Clymene dolphin from Brazil.…”
Section: Parasite Diversity and Life-cyclementioning
confidence: 99%
“…Larvae of Anisakis sp. were reported from the main stomach of a Clymene dolphin from the Caribbean coast of Mexico (Aguilar-Aguilar et al, 2010). Anisakis typica was identified using morphological and molecular tools from the stomach of Clymene dolphins in Brazil (Azevedo et al, 2017).…”
Section: Parasite Diversity and Life-cyclementioning
confidence: 99%
See 1 more Smart Citation